Analisis Komunikasi Interaksionisme Simbolik Festival: Studi Kasus Tomohon International Flower Festival (TIFF) - Kaligis, Carlita Grace Caesaria; Suharto, Bambang; Isnaini, Santi; Agustina, Tri Siwi (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
The festival is one of the activities aimed at preserving a culture. There are many different cultural festivals in Indonesia, including the Tomohon International Flower Festival (TIFF), which is a major annual event. This festival showcases the beauty of flowers and ornamental plants from all over Indonesia and from other countries as well. The purpose of this research is to analyze the symbols and meanings such as flowers, traditional clothing, dance, and music that are used to strengthen local identity and provide a unique experience for visitors. The methodology used in this research is a case study conducted on the festival held in Tomohon City, North Sulawesi, Indonesia. This research employs a qualitative-descriptive approach with data collection techniques through in-depth interviews and observation of several individuals involved in the event, such as visitors, participants, and organizers. The results show that TIFF has various cultural symbols and meanings that represent the identity of Tomohon City. Symbolic interactionism communication at the Tomohon International Flower Festival (TIFF) also creates a positive atmosphere and strengthens social relationships among them. It can be concluded that symbolic interactionism communication plays a significant role in understanding social interaction in the context of a festival. Keyword: Communication, symbolic interactionism, festival